2011
DOI: 10.4172/2155-6156.1000132
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Quality of Life Education on Self-Concept among Type 2 Diabetes Patients

Abstract: BackgroundType 2 diabetes mellitus is a chronic disease with severe late complications and high mortality. The increasing prevalence of Type 2 diabetes is mainly due to reduced physical activity and consumption of unhealthy food and larger portion sizes in genetic susceptible individuals [1], and present in every country regardless of their stage of development, and afflicts people in all socio-economic classes [2]. Longterm complications of diabetes include effects on the eyes, kidneys, nerves, and blood vess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 15 publications
1
19
0
2
Order By: Relevance
“…There is a distinct influence of hyperglycemia on the microbicidal function of macrophages, with even brief exposures to blood sugar level of 200 mg% significantly depressing the respiratory burst of these cells [69]. This is observed in poorly controlled diabetics, with high levels of glycated haemoglobin, tuberculosis follows a more destructive course and is associated with higher mortality rate [70]. Multiple pulmonary physiologic abnormalities have also been documented in diabetics that contribute to delayed clearance of infection and spread of infection in the host [71].…”
Section: Immune Dysfunction In Diabeticsmentioning
confidence: 95%
“…There is a distinct influence of hyperglycemia on the microbicidal function of macrophages, with even brief exposures to blood sugar level of 200 mg% significantly depressing the respiratory burst of these cells [69]. This is observed in poorly controlled diabetics, with high levels of glycated haemoglobin, tuberculosis follows a more destructive course and is associated with higher mortality rate [70]. Multiple pulmonary physiologic abnormalities have also been documented in diabetics that contribute to delayed clearance of infection and spread of infection in the host [71].…”
Section: Immune Dysfunction In Diabeticsmentioning
confidence: 95%
“…Patients with type 2 diabetes often have negative self-concepts, feel hopeless and, therefore, become lax about following their regimen. This study shows that quality of life education can have positive effect on diabetes self concept, and prevent physical and side effects of type 2 diabetes [52]. frequently encountered in post-stroke patients [53].…”
Section: Lifestylementioning
confidence: 66%
“…It is estimated that by 2025, 75 % of people with diabetes would be in developing countries [5] such as Iran [1]. In 2008, statistics showed that the prevalence of diabetes in Iranian urban areas is 8.6 % and in rural areas it is 5.7 % [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is the most common metabolic disorder and a major health problem all over the world [1][2][3][4]. It is estimated that by 2025, 75 % of people with diabetes would be in developing countries [5] such as Iran [1].…”
Section: Introductionmentioning
confidence: 99%